An operations process framework for international M&A value creation. (28th January 2010) - Srai, Jagjit Singh; Bertoncelj, Andrej; Fleet, Don; Gregory, Mike
A framework for understanding the operational aspects of international Mergers and Acquisitions (M&As) is presented. Based on a literature review of the operational activities that support M&As, the key stages used in the integration of manufacturing and supply networks are captured from an operations perspective. In-depth case studies of international M&As are used to explore these phases and their supporting operational processes. The resulting process map is tested and further developed with a range of operational and non-operational stakeholders, those that play critical gate-keeping roles in M&A progression. Finally, a single integrating framework is proposed, that links the 'hard' and 'soft' management factors, with the operational factors that influence successful M&A integration, and how these contribute to value creation. The framework suggests that 'network access', i.e. markets, products, technology, know-how and 'network efficiency', i.e. optimisation of manufacturing and supply chain resources, provide the two principal routes to achieving operational synergy.